FEASIBILITY ANALYSIS OF BIOGAS CHICKEN MANURE BUSINESS DEVELOPMENT (CASE STUDY AT PT JATINOM INDAH FARM): Analisis Kelayakan Usaha Pengembangan Bisnis Biogas Kotoran Ayam (Studi Kasus di PT Jatinom Indah Farm, Jawa Barat, Indonesia) - Intani Dewi; Wildan Fauzan Supriana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2020)
Gas based resource has been widely used by Indonesians on daily basis. As for cooking purposes, the use of gas in the form of LPG (Liquefied Petroleum Gas) that is distributed by the government has been considered as problematic due to the high price. On the other hand, the trend of converting to alternative energy is on the rise. Therefore, the opportunity of developing an alternative resource to replace LPG for cooking is highly demanded. Biogas is a fuel which is produced from the breakdown of organic matter such as animal manure or sewage. The highly flammable feature of methane can be utilized for cooking purpose. Biogas is cheaper than LPG and has a more reliable distribution channel. The aims of this research are to analyze the feasibility of a chicken manure biogas business in non-financial and financial aspects and to analyze the sensitivity level of the feasibility of a chicken manure biogas business. Based on financial analysis, business development at PT Jatinom Indah is feasible because it has value of NPV Rp 1 186 604 209 with NET B/C of 3,045, Gross B/C of 1,302 and IRR of 33%, with payback period 3 years and 1 month.